'Est-ce vivre?' The Politics of Living in La Boétie and Montaigne. Issue 1 (2nd January 2022) - Claussen, Emma
Abstract : This article explores Étienne La Boétie's discussion of the unfree life, with and against Montaigne's accounts of life in the Essais . In De la servitude volontaire, La Boétie responds to writing on life in his source texts, such as Seneca's 'On the Brevity of Life': the life of servitude is almost antithetical to any 'good life', and indeed is scarcely life at all. Giorgio Agamben's concept of 'bare life' and Orlando Patterson's characterisation of slavery as 'social death' elucidate La Boétie's characterisations of the deprived life in servitude. Montaigne's differently weighted reflections on painful, reduced, or tyrannised lives at the end of Book II allow that lives that are 'less than good' (not least his own, while suffering 'subjection' to kidney stones) may nonetheless be worth living. These approaches are part of the broader interest in early modern political thought in minimal definitions of the good life, and/or negative accounts of life.